2019
DOI: 10.30802/aalas-jaalas-18-000047
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of 4 Presurgical Skin Preparation Methods in Mice

Abstract: Mice routinely undergo surgical procedures for use in research; however, studies of skin preparation methods to achieve antisepsis are rare. The present study evaluated 4 skin preparation treatments: depilatory agent followed by povidone-iodine and alcohol scrub; depilatory agent followed by povidone-iodine and saline scrub; electric clippers followed by povidoneiodine and alcohol scrub; and electric clippers followed by povidone-iodine and saline scrub. Swabs for bacterial culture were obtained immediately af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…The pathological sections were obtained by Gram staining. The histological assessment was conducted by scoring pathological sections based on the criteria, including epidermal lesion, dermal inflammation, and cell proliferation. , For the first two criteria, the scores ranged from 0 (severe) to 3 (absent). For the criterion of cell proliferation, the scores ranged from 0 (absent) to 3 (prominent).…”
Section: Methodsmentioning
confidence: 99%
“…The pathological sections were obtained by Gram staining. The histological assessment was conducted by scoring pathological sections based on the criteria, including epidermal lesion, dermal inflammation, and cell proliferation. , For the first two criteria, the scores ranged from 0 (severe) to 3 (absent). For the criterion of cell proliferation, the scores ranged from 0 (absent) to 3 (prominent).…”
Section: Methodsmentioning
confidence: 99%
“…The preoperative skin preparation includes hair removal and disinfection of the surgical sites. It has been demonstrated that different disinfection methods indicated no significant differences, irrespective of depilatory agents or electric clippers depilation methods used [ 8 , 9 ]. However, in previous experiments, we have found fortuitously that mice depilated by sodium sulfide aqueous solution and scissors hair cutting methods presented some problems in the stages of wound healing.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies suggested that using clippers or depilatory cream probably results in few SSIs, compared with shaving using a razor [ 13 , 14 , 15 ]. However, some studies also indicated that both electric razor clipping and depilatory agents are safe in rats and mice [ 9 , 16 ]. Chemical depilatory can break the disulfide linkages on the keratin protein backbone by enhancing aqueous solubility, leading to hair removal [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The goal of surgical preparation is to reduce commensal bacterial load in order to prevent surgical site infections and postoperative complications such as bacterial endophthalmitis 1–6 . Surgical preparation practices in veterinary medicine are derived from human protocols identifying reductions in commensal bacteria following use of common antiseptics including chlorhexidine gluconate, povidone‐iodine, and hexachlorophene 7–11 .…”
Section: Introductionmentioning
confidence: 99%
“…The goal of surgical preparation is to reduce commensal bacterial load in order to prevent surgical site infections and postoperative complications such as bacterial endophthalmitis. [1][2][3][4][5][6] Surgical preparation practices in veterinary medicine are derived from human protocols identifying reductions in commensal bacteria following use of common antiseptics including chlorhexidine gluconate, povidone-iodine, and hexachlorophene. [7][8][9][10][11] These protocols have demonstrated similar reductions in bacterial load when used in veterinary medicine utilizing chlorhexidine gluconate, chlorhexidine diacetate, and povidone-iodine antiseptics.…”
Section: Introductionmentioning
confidence: 99%